PENINGKATAN KOMPETENSI PROFESIONALISME GURU RA MASYITOH KARANGANOM MELALUI KEGIATAN KKG GUGUS TK DI KECAMATAN PLERET KABUPATEN BANTUL 2014 (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2016)
This research is an analytical description of the improvement of teacher competence RA Masyithoh Karanganom through KKG cluster TK in Pleret of Bantul Regency, 2014, which has the aim of knowing about the efforts made to increase the competence of teachers RA masyithoh Karanganom through KKG cluster TK in Pleret. And the factors that influence it, this study is a qualitative research study focused informant to the principal, teachers at RA Masyithoh Karanganom, and chairman of the group KKG TK. The data collection is done by observation, interviews, and documentation. The results obtained in this study is the effort to increase the competence of teachers RA masyithoh Karanganom through KKG cluster TK in Pleret Bantul in a continuous effort by the teachers and the principal members of KKG TK. Impact on improving the professionalism of teachers in RA Masyitoh Karanganom Pleret Bantul.